CHALLENGES KINDERGARTEN TEACHERS FACE IN ADMINISTERING ASSESSMENT TOOLS TO CHILDREN WITH INTELLECTUAL DISABILITIES IN THE KUMASI METROPOLIS - Subbey , Michael; Muhammed, Nurudeen; Gyapong, Mark (African Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to examine the challenges kindergarten teachers face in administering assessment tools to children with intellectual disabilities in the Kumasi Metropolis. Methodology: Regarding the methodology, a descriptive survey design was adopted using a sample of 120 early childhood teachers from 22 public inclusive schools in the Kumasi Metro. Purposive sampling technique was used to select all 22 public inclusive schools, while convenience sampling technique was employed to select the actual respondents for the study. Questionnaire was used to gather the research data. Means (M) and Standard deviations (SD) were used as statistical tools to analyze the data. Findings: The findings revealed that most public kindergartens teachers in the Kumasi metropolis admitted not being confident enough to try out authentic assessments like portfolios, learning logs, journals, projects graphic organizers, concept mapping and rubrics on children with intellectual disabilities in inclusive public schools (M=3.84, SD=.575, KS=.620) due to inadequate professional guidance. It was therefore recommended that teachers should be equipped with skills and morale in administering authentic assessment practices to learners with intellectual disabilities. The study would serve as an important reference source for inclusive public and private kindergarten teachers, headmasters/mistresses, Teacher Education Division (TED), Early Childhood Care and Development Division (ECCDD) and Special Education Division(SED) of the Ghana Education Service (GES),University of Education (UEW) and the Institute of Education, (IoE) of the University of Cape Coast, (UCC) and other private educational institutions that train teachers in their effort to improve the management of testing with the adequate information about what is actually involved in assessment practices in the Early Childhood Centres. Unique contribution to theory, practice and policy: Besides, the study would contribute to the improvement of testing practices, specifically, on children with intellectual disabilities on construction, administration, and scoring of teacher-made tests in the inclusive early childhood centres. The constructivist learning theory by Lev Vygotsky, which was adopted for this study, postulated that children learn best when they are allowed to construct a personal understanding based on experiencing things and reflecting on those experiences.